2021
DOI: 10.47836/pjssh.29.s2.09
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Unfair Terms in Consumer Contracts in Malaysia and Singapore

Abstract: The inclusion of welfarist ideology in the consumers’ trade derived from the ideal of paternalism is a paradigm change from the doctrine of freedom of contract. Regulatory and legislative steps must be taken to support and attract consumers to the industry. Judicial and legislative actions must be taken to correct the market flaws that create consumers’ vulnerability while trading in the global market. As one of ASEAN members’ founders, Malaysia is moving towards people-centered economic endeavours to balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Another study compared unfair terms in consumer contracts in Malaysia and Singapore and concluded that regulatory and legislative steps must be taken to support and attract consumers to the industry. In addition, judicial and legislative actions must be taken to correct market flaws that increase consumer vulnerability while trading in the global market (Abdullah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Another study compared unfair terms in consumer contracts in Malaysia and Singapore and concluded that regulatory and legislative steps must be taken to support and attract consumers to the industry. In addition, judicial and legislative actions must be taken to correct market flaws that increase consumer vulnerability while trading in the global market (Abdullah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%